ANALYSIS OF WINDSURFING CHARACTERISTS FOR THE PHYSICAL TRAINING PRESCRIPTION (Fiep Bulletin - online, 2013)
The development of sport training programs is directly dependent on the trainer ability of knowing every details of the modality that it will be working with. One of the main questions to be investigated is about the physical trainings components that should be focused at the program. In our study, these components will be classified as: Anaerobic, Aerobic, and Flexibility. The aim of this study is to identify the physical training components of Formula Windsurfing class sailors. The research was classified as descriptive exploratory. Volunteered for this study, eight Formula Windsurfing male sailors, with at least 2 years of competition experiences, ranked at the open category of the Brazilian Windsurfing Association. Each sailor answered to a questionnaire in order to identifying the training characterizes, the time of practicing and competing in windsurfing, and also the movements' distribution on a race. In order to have the morphological profile of the athletes, an anthropometric evaluation was conducted. A case study was carried out with one of the participants of the study, in order to observe the heart rate responses of the different situations on a race. To the data analysis a statistical treatment was performed by using absolute and relative values distribution, average and standard deviation. The mean age, stature, body mass and body fat of the interviewed sailors were 36.5 ± 6.19 years, 180 ± 0.06 cm, 82.26 ± 9.74 kg and 11.90 ± 1.9% respectively. In somatotype analyses the Mesomorphic characteristic was found as dominant at most athletes. Among the sailors who perform physical training, all of them perform some bodybuilding, and furthermore, most of them are engaged also with some aerobic activity. Regarding the performed movements, was verified that in most of the elapsed time on a race, the athletes stand on an almost static position, where aerobic metabolism seems to be relevant. On the other side, when performing maneuvers, the physiological ASSOCIAÇÃO BRASILEIRA DE WINDSURF – ABWS. Modalidades. Disponível em: . Acesso em 05/04/2007. CASTAGNA, Olivier et al. The assessment of energy demand in the new olympic windsurf board: Neilpryde RS:X. European Journal of Applied Physiology, v.100, n.2, p.247-252, mai., 2007. CHAMARI, Karim et al. Correlation between heart rate and performance during olympic windsurfing competition. European Journal of Applied Physiology, v.89, n.3, 4, p.387-392, mai., 2003. CONSELHO NACIONAL DE SAÚDE. Diretrizes e normas regulamentadoras de pesquisa envolvendo seres humanos. Brasília: Ministério da Saúde, 1997. DANTAS, Estélio Henrique Martin. Prática da preparação física. 5. ed. Rio de Janeiro: Shape, 2003. FERNANDES FILHO, José. A Prática da avaliação física. Rio de Janeiro: Shape, 1999. LAROSA, Marco Antonio. Como produzir uma monografia passo a passo...siga o mapa da mina. Rio de Janeiro: Wak, 2002. LOOP WINDSURFING. Teoria On Line. Disponível em: . Acesso em: 9/04/2007. VOGIATZIS, Ioannis et al. The physiological demands of sail pumping in olympic level windsurfers. European Journal of Applied Physiology, v.86, n.5, p.450-454, mar., 2002. WIND ACTION. História do Windsurf. São Paulo, n. 2, p.28-31, jul., 1998. INTERNATIONAL FORMULA WINDSURFING CLASS ASSOCIATION – IFWCA. 2006 Championship Rules. Disponível em: Wind under 12 knots Wind above 12 knot Jibes 1,56 ± 1,24% 1,38 ± 0,86% Tacks 2,83 ± 3,42% 2,36 ± 2,63% Pumping Action 8,95 ± 9,59% 0,75 ± 0,75% Almost Static Stance 86,67 ± 9,45% 95,51 ± 3,34% Volume 79 - Special Edition - ARTICLE I - 2009 FIEP BULLETIN demand seems to increase, suggesting the involvement of anaerobic metabolism. Thus, both anaerobic and aerobic components seem to be essential to the athletes physical training. Also, a certain degree of flexibility seems to be important, especially in carrying out maneuvers.
Keywords: Physical training; Formula Windsurfing class